Evaluating Accessibility and Utilization of Tennis Facilities in Public Sports Centers: Implications for Community Engagement - Hakim, Hikmad; Ishak, Muhammad; Bismar, Ahmad Rum (JOURNAL RESPECS (Research Physical Education and Sports), 2025)
This study aims to evaluate the accessibility and utilization of tennis facilities in public sports centers and assess their implications for community engagement in Makassar City, Indonesia. Employing a mixed-methods design, the research combined quantitative surveys (n=200) and qualitative interviews (n=20) across four major public tennis venues: Karebosi, Panakkukang, Antang, and Sudiang. The primary variables examined were physical accessibility, facility utilization, demographic reach, and community participation indicators. Findings show that Karebosi Sports Center scored highest in accessibility (mean score = 8.5/10) and average weekly utilization (75 users/week), followed by Panakkukang (8.0; 62 users/week), while Antang and Sudiang scored significantly lower in both accessibility (6.4 and 6.2, respectively) and utilization (38 and 33 users/week). Facility condition and management support were significantly correlated (r = 0.71; p < 0.01) with higher utilization rates. Demographically, adults (ages 26–45) made up 52% of users, while youth (15–25) accounted for 38%, particularly high at Panakkukang due to structured youth programs. Elderly participation remained low across all sites (≤5%), signaling a lack of inclusive programming. Only 2 out of 4 facilities hosted community engagement activities (e.g., tournaments, clinics), and these were directly associated with higher user satisfaction and retention. The study concludes that infrastructure quality, inclusive programming, and active community outreach are critical in maximizing the social value of public tennis facilities. Policy recommendations include improved funding, participatory facility management, and integrated sport-for-all strategies to enhance community engagement and public health in urban Makassar.